Atomistic Simulation of La and Mn-Doped PbBi2Nb2O9 Aurivillius Phase - Akram La Kilo; Ramona Nintias R. Abas; Alberto Costanzo; Daniele Mazza; Deasy N Botutihe; Jafar La Kilo (Universitas Jenderal Soedirman, 2022)
This study aims to determine the effect of Mn3+ and La3+ dopants on the structure of PbBi2Nb2O9 (PBN) using atomistic simulation. PBN phase geometry was optimized before the Mn3+ and La3+-doped phase. Mn3+ partially substituted octahedral Nb5+ in the perovskite layer. While La3+partially substituted Bi3+ in the bismuth layer and dodecahedral Pb2+in the perovskite layer. The concentration (x) of dopants that doped PBN was made in such a way that it produces a phase of Pb1-2xBi1.5 + 2xLa0.5Nb2-xMnxO9 (x = 0, 0.1, and 0.3) which was not charged. The simulation results showed that the optimized PBN cell parameters were in a good agreement with the experimental result. Increasing the concentration of dopants result in the Pb1-2xBi1.5+ 2xLa0.5Nb2-xMnxO9 phase (PBNM-Bi and PBNM-A) being less stable, as indicated by the increased lattice energy. PBNLM-Bi structures experiences an elongation which was showed by the cell parameters of c increase while a and b decrease. La3+prefers to occupy bismuth oxide layer rather than the dodecahedral A-site of the perovskite layer. The results of this simulation can explain the PBLNM structure of experimental results that do not pay attention to the multiplicity of doped PBN with certain dopant concentrations.